2017
DOI: 10.1111/obr.12523
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid and mechanisms of actions on adipose and muscle tissue: a systematic review

Abstract: This systematic review aimed at addressing the ursolic acid actions as an adjunctive treatment of the obesity-mediated metabolic abnormalities. To explore our aims, we used the literature search including clinical and animal studies using the Medline and Google Scholar (up to December 2015). Out of 63 screened studies, 17 presented eligibility criteria, such as the use of ursolic acid on adiposity, energy expenditure and skeletal muscle mass in mice and humans. In the literature, we found that several physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 57 publications
1
21
1
1
Order By: Relevance
“…The results of the GC-MS technique in this study showed that 20.9% of the metanolic extract of SEs contained a natural pentacyclic trisperpenic acid (ursolic acid). Ursolic acid is commonly found in various parts of medicinal plants including leaves, owers, and fruits and has proven properties such as antiin ammatory, antioxidant and anti-carcinogenic properties [29]. Ursolic acid has been reported to inhibit the in ammatory factors TNF-α and IL6, LOX-1, VCAM-1, ICAM, IL5, IL13 and IL17 [30].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the GC-MS technique in this study showed that 20.9% of the metanolic extract of SEs contained a natural pentacyclic trisperpenic acid (ursolic acid). Ursolic acid is commonly found in various parts of medicinal plants including leaves, owers, and fruits and has proven properties such as antiin ammatory, antioxidant and anti-carcinogenic properties [29]. Ursolic acid has been reported to inhibit the in ammatory factors TNF-α and IL6, LOX-1, VCAM-1, ICAM, IL5, IL13 and IL17 [30].…”
Section: Discussionmentioning
confidence: 99%
“…Ursolic acid is a potent phytochemical and its use is popular in natural medicinal plants (16)(17)(18)(19)(20)(21). It has been reported that ursolic acid has anticancer effects on chemoresistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular weight of ursolic acid is 456.68 g/mole, and is a white powder that was first identified from the epicuticular wax of apples in 1920 (15). Ursolic acid is usually found in leaves, stem bark and fruit peel, and is present largely in specific plants and dietary foods, including basil, apples, peppermint, cranberries, rosemary, lavender, thyme, hawthorn, oregano, prunes, bilberries and elderflower (16)(17)(18). Ursolic acid has been used for its health-promoting activities via the composition of herb extracts applied in popular medicines for centuries (19)(20)(21).…”
Section: Ursolic Acid Elicits Intrinsic Apoptotic Machinery By Downrementioning
confidence: 99%
“…Polycyclic triterpenes are metabolites of vegetable origin that have 30 carbon atoms in their structure, constituted by six units of isoprene, these metabolites can be found in their free state or in the form of glucoside 3 of which are distinguished by ursolic acid by its numerous pharmacological and therapeutic properties, known as urson, prunol, micromerol and malol (acid (3B) -3-hydroxy-urs-12-en-28-oico), 5 present in different plants, such as barks, stems, leaves or peels fruit, 6 formed from two molecules of acetyl CoA, its synthesis is divided into three phases, 9,10 ursolic acid has been closely related to the body substance that has an effect on the percentage of fat mass and muscle mass .…”
mentioning
confidence: 99%